The legal critiques of the computer crimes act 1997 in regulating cyber crime / Zaiton Hamin, Hartini Saripan and Rafizah Abu Hassan - Hamin, Zaiton; Saripan, Hartini; Abu Hassan, Rafizah (Faculty of Law, 2011)
From the practical legal perspective and engaging at the instrumental and normative levels, this research attempts to focus on the legal critiques of the Computer Crimes Act 1997. In particular, on the question of what is cyber crime, why is reform needed to the substantive provisions of the said Act and what changes are sought for as well as the rationales in reforming the said Act. Issues affecting the degree or kind or both that drive the need for reform of the 1997 Act will be also be discussed. In line with the approach of common law jurisdictions, in particular the United Kingdom and Singapore as well as the Cyber crime Convention 2001, the research will examine the problems of substantive law, specifically the provisions that may be inadequate to cover certain cyber crimes such as distributed denial of service and the provisions that may in fact cover too wide an area of conduct. Also, from the theoretical level, philosophical issues involved in cyber crime, in particular the problem of identifying legal interests and emerging legal interests will be examined. Adopting a doctrinal and library-based research approach with content analysis as the research design, this current research proposes to scrutinize the 1997 Act in comparison with its Singapore and the United Kingdom counterparts, Computer Misuse Act 1993 and the Computer Misuse Act 1990 respectively. A cursory look at the Communications and Multimedia Act 1998 would also be necessary to examine if the former statute have adequately supplemented the 1997 Act. The Council of Europe Cyber crime Convention 2001, a significant piece of international instrument, which is broadly aimed at harmonizing cyber crime laws around the world, will also be critically examined to determine the extent to which the 1997 Act in its current form is in keeping with this Convention.